2014
DOI: 10.1208/s12248-014-9664-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Arctigenin Pharmacokinetics After Intravenous and Oral Administrations in Rats: Integration of In Vitro and In Vivo Findings via Semi-mechanistic Pharmacokinetic Modeling

Abstract: Abstract. Although arctigenin (AR) has attracted substantial research interests due to its promising and diverse therapeutic effects, studies regarding its biotransformation were limited. The current study aims to provide information regarding the pharmacokinetic properties of AR via various in vitro and in vivo experiments as well as semi-mechanistic pharmacokinetic modeling. Our in vitro rat microsome incubation studies revealed that glucuronidation was the main intestinal and liver metabolic pathway of AR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
4
13
0
Order By: Relevance
“…However, due to the much higher oral dose, the uptake of veratramine-3-O-sulfate into bile canaliculi may be slower than the formation of veratramine-3-O-sulfate in the hepatocytes, thus, veratramine-3-O-sulfate was found in plasma and urine in addition to bile. Such explanation for the potential routedependent disproportionate increase of parent compounds and metabolites across doses due to saturation of biliary excretion was also found in previous studies (74,75). Moreover, although the gender differences on the malepredominant urinary accumulation of 7-hydroxyl-veratramine and female-predominant biliary excretion of veratramine-3-O-sulfate were distinct after both oral and i.v.…”
Section: Discussionsupporting
confidence: 81%
“…However, due to the much higher oral dose, the uptake of veratramine-3-O-sulfate into bile canaliculi may be slower than the formation of veratramine-3-O-sulfate in the hepatocytes, thus, veratramine-3-O-sulfate was found in plasma and urine in addition to bile. Such explanation for the potential routedependent disproportionate increase of parent compounds and metabolites across doses due to saturation of biliary excretion was also found in previous studies (74,75). Moreover, although the gender differences on the malepredominant urinary accumulation of 7-hydroxyl-veratramine and female-predominant biliary excretion of veratramine-3-O-sulfate were distinct after both oral and i.v.…”
Section: Discussionsupporting
confidence: 81%
“…The formation of AR‐4′‐O‐glucuronidation could also be observed in HIM, which is consistent with previous report that AR could be transformed to its 4′‐O‐glucuronide in rat intestine microsomes [21]. The kinetic analysis demonstrated that human intestine played an important role in AR‐4′‐O‐glucuronidation with Cl int value of 776 μl/min/mg protein in HIM, implying that AR may undergo a first‐pass metabolism during the absorption process.…”
Section: Discussionsupporting
confidence: 92%
“…This could be partially explained by the fact that rat UGT1A9 is a pseudogene and the propofol O‐glucuronidation activity in rat liver is much lower than that in human liver [22,23]. These findings agreed well with the observation of rapid formation of 4′‐O‐glucuronide after both oral and IV administration of AR,[21] indicating that AR may be rapidly eliminated from human body via glucuronidation pathway.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It is reported that AG can be metabolized to be arctigenic acid and arctigenin-4′- O -glucuronide in rats’ plasma by oral administration (Gao et al, 2014a). And there were different tissue distribution in SD rats (He et al, 2013).…”
Section: Introductionmentioning
confidence: 99%